KESIAPSIAGAAN BENCANA PERAWAT PUSKESMAS DI KABUPATEN MALANG: NURSE DISASTER PREPAREDNESS IN A PUBLIC HEALTH CENTER OF MALANG REGENCY - Wahyudi, Yuyud (WELL BEING, 2025)
Disaster preparedness is an effort made to carry out emergency planning, advice and infrastructure, resources, etc. in the event of a disaster at any time. The purpose of this study is to describe the preparedness of nurses to face disasters in the working area of the Dampit Public Health Center, Malang Regency. The research design used a descriptive method with a cross sectional approach qith a. The research sampling technique of this research is total sampling as many as 17 respondents with the research instrument in the form of a questionnaire. The research variable of this research is in disaster preparedness (nurse preparedness to face disaster). The validity test of this study using the I-CVI (Content Validity Index) obtained a value of 0.954 is declared valid. The research reliability test used Cronbach's alpha with a result of 0.682, this shows that the items are reliable. The results of the study showed that 100% of nurses had good knowledge and attitudes, 100% of policies at the Dampit Public Health Center were good, 100% had good emergency planning, 70.6% had a poor warning system, and 100% had good resource mobilization. The conclusion of this study is that the preparedness of nursing ini dealing with disaster based on the preparedness variables has a good category.